Efficacy and safety of 10,600 nm fractional carbon dioxide laser versus 88% phenol in treatment of idiopathic guttate hypomelanosis: A prospective study - K Deepadarshan; M R Harish; B M Shashikumar; Priyanka R Chandran (Wolters Kluwer Medknow Publications, 2022)
Background: Idiopathic guttate hypomelanosis (IGH) is a common benign acquired leukodermic dermatosis characterized by multiple, discrete, hypopigmented-to-depigmented macules. Various treatment modalities were tried for this condition with varied results. Purpose: This study was conducted to compare the efficacy and safety of fractional carbon dioxide laser and 88% phenol in the treatment of IGH. Methods: A total of 40 patients with five IGH macules on each side were treated with one session of fractional carbon dioxide laser on the right side and a single application of 88% phenol on the left side and were assessed monthly for 3 months. The improvement in pigmentation was graded as ≤25% - poor, 26%-50% - minimal, 51%-75% - good, and >75% - excellent response. Results: A total of 32 patients completed the study. Out of the 160 macules treated with laser, 16 (10%) macules showed an excellent response and 40 (25%) showed a good response, and 40 (25%) and 48 (30%) macules in the phenol group showed excellent and good improvement, respectively. Side effects such as persistent scabbing and ulceration were seen only on the phenol side. Conclusion: Single application of 88% phenol was more efficacious than one session of fractional carbon dioxide laser in inducing pigmentation in IGH macules in this study. However, fractional carbon dioxide laser can be considered a safer alternative modality.